2021
DOI: 10.1093/abbs/gmab102
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomal miR-21a-5p promotes M2 macrophage polarization and reduces macrophage infiltration to attenuate atherosclerosis

Abstract: Atherosclerosis (AS) is the main pathological basis for ischemic cardiovascular and cerebrovascular diseases. Mesenchymal stem cell (MSC)-derived exosomes have the potential to alleviate AS, while the underlying mechanism remains unclear. Here, we aimed to investigate the mechanism of MSC-derived exosomes in AS. The AS mouse model was prepared by feeding ApoE–/– mice with high-fat diet. AS mice were administered with MSC-derived exosomes, and the atherosclerotic plaque area was analyzed by Oil Red O staining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…let-7 reduces macrophage migration by targeting insulin-like growth factor 2 mRNA binding protein1 (IGF2BP1), which regulates the PTEN pathway and induces M2 polarization by targeting the high mobility group AT-hook 2 (HMGA2) responsible for regulating the NF-κB pathway. Ma et al, found that miR-21a-5p is also highly expressed in MSC-derived exosomes and that miR-21a-5p induces M2 polarization by targeting KLF6 and ERK2, whereas it reduces macrophage migration by targeting ERK2 [67]. Collectively, this further implicates MSC-derived exosomes containing miR-100-5p, miR-512-3p, let-7 family, and miR-21a-5p as therapeutic agents for atherosclerosis.…”
Section: Exosomes Derived From Mscmentioning
confidence: 96%
“…let-7 reduces macrophage migration by targeting insulin-like growth factor 2 mRNA binding protein1 (IGF2BP1), which regulates the PTEN pathway and induces M2 polarization by targeting the high mobility group AT-hook 2 (HMGA2) responsible for regulating the NF-κB pathway. Ma et al, found that miR-21a-5p is also highly expressed in MSC-derived exosomes and that miR-21a-5p induces M2 polarization by targeting KLF6 and ERK2, whereas it reduces macrophage migration by targeting ERK2 [67]. Collectively, this further implicates MSC-derived exosomes containing miR-100-5p, miR-512-3p, let-7 family, and miR-21a-5p as therapeutic agents for atherosclerosis.…”
Section: Exosomes Derived From Mscmentioning
confidence: 96%
“…MSC-derived exosomes containing miR-21A-5p promoted M2 polarization of RAW264.7 cells by inhibiting KLF6 expression and inhibited migration of RAW264.7 cells by inhibiting the ERK1/2 signaling pathway. The miR-let7/HMGA2/NF-κB pathway promoted the polarization of M2 macrophages in plaques, while the miR-let7/IGF2BP1/PTEN axis inhibited the infiltration of macrophages 128 , 129 . Therefore, MSC-derived exosomes are expected to be developed as a therapeutic agent for AS.…”
Section: Macrophage-associated Exosomes In Arteriosclerosismentioning
confidence: 98%
“…The most common 2D in vitro models are single-cell culture systems, which contain only one type of cell component observed in the atherosclerotic plaque, such as ECs, SMCs, macrophages, and foam cells. Single-cell cultures have been used to assess new types of therapeutics, such as microRNA (35,36) and exosomes (37,38), and investigate mechanistic studies associated with atherosclerosis. However, recently they have been widely applied for evaluating the efficacy of drug-loaded delivery systems for treating atherosclerosis due to the issues observed in free drug administration (Table 1).…”
Section: In Vitro 2d Models For Atherosclerosis Studiesmentioning
confidence: 99%